All Days 2003
DOI: 10.4043/15244-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Spar and Vortex Induced Vibrations

Abstract: Vortex Induced Vibrations (VIV) of Spars under current flow is an important consideration of Spar mooring design. Model tests and Field data show that Spar VIV is a complex issue that can involve a large number of parameters which include Spar hull characteristics, dynamic characteristics of the moored system and current characteristics itself (profile, turbulence, direction). The Cell Spar is a new design that has several physical characteristics that are different than those of the present classic and truss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Evaluation of vortex induced motion (VIM) in offshore floating structures has been largely been carried out for spars. Classic spar, truss spar and cell spar hulls are all known to exhibit VIV (VIM) [1], [2], [6], [7], [8], [9], [10], [12], [13], [14], [15], [16], [19], [27], [28], [29]. [31], [32],…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of vortex induced motion (VIM) in offshore floating structures has been largely been carried out for spars. Classic spar, truss spar and cell spar hulls are all known to exhibit VIV (VIM) [1], [2], [6], [7], [8], [9], [10], [12], [13], [14], [15], [16], [19], [27], [28], [29]. [31], [32],…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, despite focused on mitigating the effects of VIM on such a type of platform by adding strakes, those authors also showed that, without suppressors, the maximum response amplitude occurs in a range of reduced velocities between 5 and 9, making explicit mention to eight-shaped trajectories, in a quite evident coupling between the in-line and transverse motions. Additionally, experiments by Finn et al [2] established a direct relationship between hull geometry and VIM response, highlighting the correlation between towing tests and those performed at water channels. According to those results, a formal procedure for testing VIM on spar-type platforms was presented in Irani and Finn [3], including concerns about the right consideration of the restoring system in small-scale tests.…”
Section: Introductionmentioning
confidence: 95%
“…A third generation spar, the ''cell spar'', was installed for in 2004 (Finn et al 2003). This design embodies a new construction technique using ring stiffened tubulars assembled in a hexagonal formation to form a spar.…”
Section: Spar Hull Sizing Parametersmentioning
confidence: 99%